Safety netting in healthcare settings: what it means, and for whom? - Roland, D; Jones, C; Neill, S; Thompson, M; Lakhanpaul, M (2014)
Everyday thousands of children are presented to health care practitioners by concerned parents with the vast majority being simple self-limiting illness. However serious bacterial illness, chronic inflammatory conditions and mental health problems are repeatedly missed with significant morbidity, mortality, financial and social implications. A conceptual framework detailing the mechanism of effective Safety Netting has yet to be described however and there is increasing evidence parents want guidance on when to seek medical advice (a key part of safety netting) prior to initial consultation. This article explores current understanding of safety netting in relation to child health and argues there is a need to develop a more standardised approach.